Pengaruh NAA dan BAP terhadap Kultur Jaringan Nenas Tangkit (Ananas comosus (L.) Merr. cv. Tangkit) - Neliyati NELIYATI; Zulkarnain ZULKARNAIN (Universitas Jambi, 2017)
This study was aimed at investigating the effect of NAA and BAP on the development of basal slip slices in tissue culture of pineapple cv. Tangkit. The experiment was conducted at the Plant Biotechnology Laboratory Agricultural Faculty University of Jambi from July through to October 2016. Six level of NAA concentrations (0, 1, 2, 3 , 4 and 5 mgL-1) were tested in combination with six levels of BAP concentration (0, 1, 2, 3 , 4 and 5 mgL-1). A Completely Randomized Design with 5 replicates was employed in this trial. Data on the percentage of explants forming shoots, time required for shoot formation, number of shoots growing per explants, and callus proliferation were recorded. Results showed that without the involvement of plant growth regulators there had been no growth on cultured explants. However, shoot growth was found on explants cultured on medium supplemented with 1 – 3 mgL-1 NAA or 1 – 5 mgL-1 BAP. The application of NAA higher than 3 mgL-1 was found to suppress shoot growth even in combination with BAP. Shoot formation was found to be fast on medium supplemented with 1 mgL-1 NAA + 4 mgL-1 BAP, but took longer time on medium with or 1 mgL-1 NAA + 5 mgL-1 BAP as well as medium with 1 – 2 mgL-1 NAA only. The same phenomenon was also found on medium with 1 – 2 mgL-1 NAA only. This study also revealed that most of cultured explants regenerated only one shoot, but explants cultured on medium with 1 mgL-1 NAA along with 1 mgL-1 BAP produced 2.33 shoots on the average. The addition of 1 mgL-1 NAA without BAP and 1 mgL-1 BAP without NAA could increase average shoot growth by 1.78 and 1.44, respectively. Keywords: in vitro culture, micropropagation, naphthalene acetic acid, benzyl amino purine.